Self‐reported stigmatisation among patients with atopic dermatitis (AD) or chronic spontaneous urticaria (CSU): A cross‐sectional study - Malthe A. K. Wiis; Sofine Heilskov; Jennifer A. Sørensen; Karen Bang; Henrik Egekvist; Mette Deleuran; Jacob P. Thyssen; Simon F. Thomsen; Christian Vestergaard (Wiley, 2022)
Abstract Background Atopic dermatitis (AD) and chronic spontaneous urticaria (CSU) are two prevalent, visible and itching skin diseases associated with decreased quality of life (QoL), sleep disturbance, depression and anxiety. However, little is known about stigmatisation among patients suffering from these diseases. Objectives To examine whether patients with AD or CSU experience stigmatisation and if disease severity or psychosocial variables associate with experienced stigmatisation. Methods A cross‐sectional survey was performed among adult AD and CSU patients from two highly specialised university hospitals and two private dermatology clinics. External stigmatisation was examined using the 6‐item Stigmatisation Scale (6SS). AD severity was assessed by dermatologists using the Eczema Area and Severity Index (EASI) score. Patient‐reported outcome measures (PROMs) included: Patient‐Oriented Eczema Measure, Urticaria Activity Score over 7 days (UAS7), Urticaria Control Test, Dermatology Life Quality Index, 9‐item Patient Health Questionnaire, 7‐item Generalised Anxiety Disorder, Insomnia Severity Index and Work Productivity and Activity Impairment Questionnaire: General Health. Nonparametric statistics were used due to nonnormal distribution of data. Data were managed in REDCap and analysed with Stata for macOS. Results Mean EASI score was 7.6 (±10.7) and the mean UAS7 score was 15.6 (±12.0), for patients with AD and CSU, respectively. External stigmatisation was reported by 78.6% of AD patients and 57.3% of CSU patients. Mean 6SS score was 2.9 (±2.8) among AD patients and 1.9 (±2.8) among CSU patients, and stigmatisation levels differed significantly (p < 0.001). In both AD and CSU patients, stigmatisation correlated weakly to moderately with sleep disturbance (rs = 0.48 and rs = 0.30) and symptoms of depression (rs = 0.50 and rs = 0.38) and anxiety (rs = 0.46 and rs = 0.36), but not with disease severity as measured by EASI and UAS7. Conclusion Both AD and CSU patients report external stigmatisation, which correlated with psychological parameters but not with disease severity. Further studies on stigmatisation are needed and should include a standardised scale embracing both external and internal facets of stigmatisation.